Social media as taste re-mediators: emerging patterns of food taste on TripAdvisor. (26th May 2020) - Onorati, Maria Giovanna; Giardullo, Paolo
ABSTRACT: The current contribution provides insight into the transformations occurring in food taste and in gastronomy standards, where social media contributes to assess eating out in situations of mobility. The coalition between food and new media has brought about new priorities and standards in taste, relying less on proper gastronomic expertise than on media dynamics and 'metamorphic' claims of social distinction in these times of cultural omnivorousness. On this basis, the paper looks into emerging taste patterns, outlined by the widespread practice of sharing restaurant reviews on travel social media. It addresses both eating out and social media as an open set of social practices that, though highly dynamic and internally differentiated, speak for collective and socially organized patterns of behaviors, so as to become entry points to grasp broader social dynamics dwelling in connectivity, gastronomy, food consumption. To this aim, the study analyses TripAdvisor's reviews of the restaurants in the Italian region Aosta Valley in a time span of 25 months. The analysis highlights the process of food taste "re-mediation" played by social media and the emergence of a culinary capital based on plastic habitus and a plural socialization to food that ranges from TV foodtainment to digital narratives, to new patterns of aware eating.